How Resilient is Public Support for Carbon Pricing? Longitudinal Evidence from Germany - Stephan Sommer; Théo Konc; Stefan Drews (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
The success of climate policies depends crucially on the dynamics of public support. Using unique longitudinal data from three surveys conducted between 2019 and 2022, we study the variations of public support for carbon pricing in Germany. The period includes two relevant events: the introduction and ramping up of carbon pricing in Germany and the exogenous increase in energy prices following the Russian invasion of Ukraine. Using panel methods, we show that support is very persistent over time and might have increased slightly more recently. However, people who experience high energy costs display a lower support. Regarding revenue use, we detect that social cushioning has become more popular after the introduction of carbon pricing. Our findings suggest that it is crucial to gather enough support before implementing climate policies.
Keywords: D12; H23; Q58; 330; Climate change mitigation; political economy; panel methods